Adiponectin in children on peritoneal dialysis: Relationship to insulin resistance and nutritional status - Kamariski, Mariana (2009)
Aim: To study whether adiponectin and resistin serum concentrations in children on peritoneal dialysis (PD) were related to insulin resistance (IR) and anthropometric parameters of nutritional status, 11 PD patients, 9 chronic kidney disease (CKD) patients and 10 healthy children were studied. Methods: Glucose and insulin were measured during the oral glucose tolerance test. Levels of adiponectin and resistin were evaluated by ELISA, insulin by RIA. Results: In CKD patients, higher homeostasis model assessment-insulin resistance (HOMA-IR), fasting and 2-hour serum insulin levels were shown compared to control and to PD patients. Body mass index (BMI) and body fat content were severely decreased while serum adiponectin levels were significantly higher in PD patients relative to controls. No differences among groups were shown in resistin levels. On regression modeling, inverse independent associations were observed between adiponectin with percentile BMI, weight and height z-score, and with body fat content. In contrast, no relationship was found between adiponectin and IR parameters. In multiple regression analysis, adiponectin was negatively correlated with BMI. A negative association of adiponectin and resistin with glomerular filtration rate was also shown. Conclusion: A role for adiponectin in terms of its association with clinical wasting parameters in PD pediatric patients might be suggested.